Investigating of Language Errors in the Field of Morphology in Scientific Articles of Seribu Bukit State High School Students - Fitriani, Ria; Pohan, Jusrin Efendi; Dian Syahfitri, Dian (Universitas Muria Kudus, 2024)
This research aims to describe the forms of language errors in the field of morphology in scientific articles by Seribu Bukit state high school students. The research data is in the form of 27 student scientific articles. The method used in this research is a qualitative descriptive method. The analysis technique used is the test technique. The test is in the form of a scientific article. Students are asked to write scientific articles. The results of this research show that the forms of morphological errors found in scientific articles of class not standard. The form of error in the field of reduplication lies in its redundant/pleonic use. The form of a composite error lies in the procedure for writing it. The findings of this research show that language errors in the morphological aspect are found in grammatical errors, diction errors, affixation errors, and composite errors.